Advanced Mechatronic Systems Featuring Pneumatic Actuation - Šitum, Željko; Čavić, Filip; Pavlović, Vid; Zoričić, Lovro; Ivanković, Ante; Čmelješević, Matija; Galić, Bernarda; Prgomet, Mia; Varović, Antonio (International Conference Fluid Power 2025: Conference Proceedings, 2025)
This article presents eight innovative mechatronic systems powered by pneumatic actuators, designed as educational models for teaching pneumatic power systems and automatic control to mechanical engineering students. The first system introduced is a prototype of an autonomous vehicle that operates on compressed air and is driven by pneumatic artificial muscles. Next, four robotic systems are described, representing pneumatically actuated manipulators. These include a delta robot with a vacuum gripper, a robotic arm with a flexible gripper, a manipulator capable of avoiding obstacles on a conveyor belt, and a flexible pneumatic manipulator. The final section highlights three systems with potential industrial applications: a pneumatically powered screw mechanism, a system for automated bottle filling and capping, and an automated pneumatic machine designed to sort beans. All eight systems provide practical insights into the application of pneumatics in automation and serve as valuable tools for hands-on learning in mechatronics and control engineering.